Pengaruh Self-Confidence terhadap Hasil Belajar Al-Qur’an Hadis Siswa Kelas VII di MTsN 1 Payakumbuh - Khairi, Hayatul; Rahmi, Siska Yulia (TSAQOFAH, 2025)
This study aims to investigate the influence of self-confidence on student learning outcomes in the Al-Qur’an Hadith subject among seventh-grade students at MTsN 1 Payakumbuh. A quantitative approach was employed, with data collected through questionnaires and observations involving 97 respondents. The results reveal that: (1) students' level of self-confidence falls into the moderate category, with a percentage of 73.19%; (2) student learning outcomes in Al-Qur’an Hadith are classified as very good, with a percentage of 66%; and (3) there is a significant relationship between self-confidence and academic performance. Hypothesis testing yielded a significance value of 0.000 < 0.05 and a t-value of 3.851 > tₜₐᵦₗₑ 1.985, leading to the rejection of H₀ and the acceptance of Hₐ. Accordingly, it can be concluded that self-confidence has a positive effect on student learning outcomes, contributing 13.3% to the variance. These findings indicate that reinforcing self-confidence within the learning process can enhance students’ academic achievement in Al-Qur’an Hadith. The implication is that teachers should adopt pedagogical strategies that encourage active participation and foster students’ self-belief in religious education contexts.